FACTORS AFFECTING LEARNERS’ SATISFACTION WITH AN ONLINE ENGLISH LEARNING COURSE IN VIETNAM (Journal of Foreign Language Studies, 2020)
This study examines factors that influence learners’ satisfaction with an online English learning course implemented at a Vietnamese university. The researcher utilizes mix-methods approach, exploratory factor analysis, linear regression and deductive analytical techniques to analyze a set of quantitative and qualitative data. The findings of the study indicate that factors related to an online course could be divided into two groups concerning the online course and learners. Factors about the online course were its usefulness, Internet quality and delivery while those concern the learners were their self-regulations and language proficiency.
Keywords: Self-regulation; usefulness; factor analysis; satisfaction; interaction; Vietnam